Fulfillment of Learnes’ Learning Need Through Differentiation in Indonesian Language Learning in SDN Sondakan Surakarta - Efendi, Fauzi Habib; Amalia, Nur (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
Classroom learning is mostly still beating students' abilities, while students' abilities vary, so that learning methods are needed that are in accordance with the abilities of each student. Education in Indonesia requires an increase that is able to provide enlightenment, with yesterday's covid 19 making student learning disrupted. Differentiated learning is a new learning system following the times that is expected to provide rapid change for education in Indonesia. This study aims to describe differentiated Indonesian language learning for students in grade IV elementary school. This research uses descriptive qualitative. Data collection techniques in this research are observation, interview, and documentation. The results of this study are the application of differentiated learning at SDN 11sondakan Surakarta, in grade IV Indonesian language learning, and the impact of the application of differentiated learning at SDN 11 Sondakan Surakarta on grade IV Indonesian language learning. The conclusion of this research is that differentiated learning refers to an approach that considers the individual needs, interests, and abilities of students. The most important component is understanding the ability of individual students. The results of differentiated learning are more improved than before.